Study of Prescription-Indication of Outpatient Systemic Anti-Fungals in a Colombian Population. A Cross-Sectional Study - Luis Fernando Valladales-Restrepo; Juan Alberto Ospina-Cano; Brayan Stiven Aristizábal-Carmona; Diana Fiorella López-Caicedo; Melissa Toro-Londoño; Andrés Gaviria-Mendoza; Manuel Enrique Machado-Duque; Jorge Enrique Machado-Alba (MDPI AG, 2022)
The inappropriate use of antifungals is associated with greater antimicrobial resistance, costs, adverse events, and worse clinical outcomes. The aim of this study was to determine prescription patterns and approved and unapproved indications for systemic antifungals in a group of patients in Colombia. This was a cross-sectional study on indications for the use of systemic antifungals in outpatients from a drug dispensing database of approximately 9.2 million people affiliated with the Colombian Health System. Sociodemographic, pharmacological, and clinical variables were considered. Descriptive, bivariate, and multivariate analyses were performed. A total of 74,603 patients with antifungal prescriptions were identified; they had a median age of 36.0 years (interquartile range: 22.0-53.0 years), and 67.3% of patients were women. Fluconazole (66.5%) was the most prescribed antifungal for indications such as vaginitis, vulvitis, and vulvovaginitis (35.0%). A total of 29.3% of the prescriptions were used in unapproved indications. A total of 96.3% of ketoconazole users used the medication in unapproved indications. Men (OR: 1.91; CI95%: 1.79-2.04), <18 years of age (OR: 1.20; CI95%: 1.11-1.31), from the Caribbean region (OR: 1.26; CI95%: 1.18-1.34), with chronic obstructive pulmonary disease (OR: 1.80; CI95%: 1.27-2.54), prescriptions made by a general practitioner (OR: 1.17; CI95%: 1.04-1.31), receiving comedications (OR: 1.58; CI95%: 1.48-1.69), and the concomitant use of other antimicrobials (OR: 1.77; CI95%: 1.66-1.88) were associated with a higher probability that the antifungal was used for unapproved indications; deep mycosis (OR: 0.49; CI95%: 0.41-0.58), prescribing fluconazole (OR: 0.06; CI95%: 0.06-0.06), and having diabetes mellitus (OR: 0.33; CI95%: 0.29-0.37), cancer (OR: 0.13; CI95%: 0.11-0.16), or HIV (OR: 0.07; CI95%: 0.04-0.09) reduced this risk. Systemic antifungals were mostly used for the management of superficial mycoses, especially at the gynecological level. In addition, more than a quarter of patients received these medications in unapproved indications, and there was broad inappropriate use of ketoconazole.